Etika Kepribadian Hakim di Mahkamah Agung dan di Mahkamah Konstitusi - Faiz Redha Alfansuri; M. Azhar Al Anshori; Iswatus Saidah (JURNAL ILMIAH NUSANTARA, 2024)
This abstract focuses on the moral responsibility of constitutional judges in Indonesia to remain faithful to constitutional values and uphold independence. The Constitutional Court (MK) functions as a protector of moral values within Pancasila and the constitution, including maintaining the nation's morality in line with these values. Some MK decisions have used constitutional morality as a benchmark, though there are instances where this morality has been overlooked. Cases of ethical violations by constitutional judges highlight the urgent need to build constitutional morality, especially in the judge selection process. The moral requirements in judge selection need to be sharpened to ensure judges possess high integrity, honesty, and independence, free from personal interests and external pressures. This study aims to identify and address the ethical challenges faced by judges in performing their duties, to ensure fair and integrity-driven law enforcement in Indonesia.